"Lost" causes : agenda vetting in global issue networks and the shaping of human security - Carpenter, R. Charli (Cornell University Press, 2014)
Why do some issues and threats--diseases, weapons, human rights abuses, vulnerable populations--get more global policy attention than others? How do global activist networks decide the particular causes for which they advocate among the many problems in need of solutions? According to Charli Carpenter, the answer lies in the politics of global issue networks themselves. Building on surveys, focus groups, and analyses of issue network websites, Carpenter concludes that network access has a direct relation to influence over how issues are ranked. Advocacy elites in nongovernmental and transnational organizations judge candidate issues not just on their merit but on how the issues connect to specific organizations, individuals, and even other issues. In "Lost" Causes, Carpenter uses three case studies of emerging campaigns to show these dynamics at work: banning infant male circumcision; compensating the wartime killing and maiming of civilians; and prohibiting the deployment of fully autonomous weapons (so-called killer robots). The fate of each of these campaigns was determined not just by the persistence and hard work of entrepreneurs but by advocacy elites' perception of the issues' network ties. Combining sweeping analytical argument with compelling narrative, Carpenter reveals how the global human security agenda is determined